Ultrasonic intensification of aerobic stabilization of sewage sludge = Ultradźwiękowa intensyfikacja stabilizacji tlenowej osadów ściekowych - Sorys, Piotr; Zielewicz, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aerobic stabilization of excess sewage sludge using low frequency ultrasound (25kHz) was investigated. The mechanically thickened excess sludge was obtained from full-scale wastewater treatment plants. The samples of sewage sludge were prepared by dissolving drinking water to obtain initial total solid concentration of 1800 mg/dm3.
Keywords: osady ściekowe; biologiczna oczyszczalnia ścieków; sewage sludge; wasterwater treatment plants